2017
DOI: 10.5604/01.3001.0010.1881
|View full text |Cite
|
Sign up to set email alerts
|

AIDS and nutrition in patients

Abstract: Introduction: AIDS is a viral infection that particularly affects the nutritional status of patients by complicating the absorption of nutrients and their metabolism. Purpose: The purpose of this retrospective study is to highlight the contribution of nutrition to the wellness of people with HIV in all stages of the disease. Review Methods: The methodology used to select the information used in this study includes review studies and research in leading databases such as PUBMED, MEDLINE, and IATROTEK. The selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
2
0
1
Order By: Relevance
“…Furthermore, a vaccine that will provide preventive protection against HIV/AIDS is the big issue in research on the disease from the very first years of the onset of the disease. [27] Compliance with ethical standards…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a vaccine that will provide preventive protection against HIV/AIDS is the big issue in research on the disease from the very first years of the onset of the disease. [27] Compliance with ethical standards…”
Section: Discussionmentioning
confidence: 99%
“…Among these challenges, nutrition is a crucial factor that can impact morbidity and mortality in older PLWH. Previous studies showed that nutrition can enhance the immune system response to HIV replication and that malnourished PLWH were more likely to develop opportunistic infections than those with adequate nutrition [ 4 , 5 ]. It is widely believed that malnutrition, the immune system of PLWH, and HIV infection are intertwined and that the former two factors affect the outcome of the latter [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Desde el momento en que la desnutrición hospitalaria fue puesta en la mira del ámbito científico en 1974 por la investigación del Dr. Charles Butterworth y su artículo "El esqueleto en el armario del hospital" (1) y reconocida como factor de riesgo para complicaciones, aumento en la estancia hospitalaria, reingresos, fracasos terapéuticos e incremento en los costos de salud (2)(3)(4) , se fue despertando la conciencia de su impacto en diferentes patologías (5)(6)(7)(8) .…”
Section: Introductionunclassified